PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIA SD NEGERI 158 PEKANBARU - Dewi Marlina; Erlisnawati '; Zulkifli ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on beginning observation author does, that is in social science study stills teacher domination existence uses lecture method inclined boring, besides undercommunication will involve student activity in will do study activities should student can touch direct with things that activity that be done, so that result learns student balum increase. this watchfulness is done at class iiia country elementary school 158 Pekanbaru school year 2014/2015. this watchfulness design class action watchfulness. class action watchfulness practise watchfulness that aim to repair deficits in study at class with do certain actions so that can repair and or increase study practices at class according to more professional. subjek this watchfulness class student IIIa semester 2 school year 2014/2015 at country elementary school 158 Pekanbaru with total 26 person. from watchfulness result be be known to concluded type co-operative study model applications word square can increase result learn class student social science iiia country elementary school 158 pekanbaru. Result learns student after study repair in second cycle is better. where is student complete in my cycle as big as 62% or increase as big as 23.08% compared beginning score. while in comparison with daily repetition score 2, complete student as big as 81% or rise to be 42.31%.Key Words: Word square, students Achievement Social Studies.